PERKEMBANGAN PENELITIAN PENGELOLAAN HOTEL BERBASIS SMART TECHNOLOGY: ANALISIS BIBLIOMETRIK DENGAN PENDEKATAN CO-OCCURRENCE, CO-CITATION, DAN BIBLIOGRAPHIC COUPLING - I Made Bayu Wisnawa (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2026)
The development of smart technology has driven a significant transformation in the management of the hospitality industry. Studies on smart technology in hotel management continue to grow, but comprehensive mapping of the structure, development, and direction of research is still limited. This study aims to analyze the development of smart technology-based hotel management research through a bibliometric approach. Research data was obtained from the Scopus database with a publication range of 2010–2025, which resulted in 68 scientific papers. The analysis was carried out using VOSviewer software by applying keyword co-occurrence techniques, overlay visualization, co-citation analysis, and bibliographic coupling. The results of the study show that the thematic structure of hotel management research is still dominated by the context of the hospitality industry in general, with smart technology playing a role as a supporting instrument for operational management. However, in recent years, the focus of research has shifted towards the use of smart technology as a driver of innovation and sustainability in the hospitality industry. The co-citation analysis reveals that the intellectual foundation of this research rests on the hospitality management literature and qualitative methodological approaches, while bibliographic couplings show that the current research direction is moving towards integration between technological innovation, sustainability, and hotel performance. This research provides an academic contribution by mapping the development and direction of smart technology research in hotel management, as well as practical implications for industry players in designing innovation- and sustainability-oriented digital transformation strategies.